Attitude of wheat growers towards Pradhan Mantri Fasal Bima Yojana - TANWAR, AKASH; KAUR, MANMEET; RATHORE, SURYA (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out during 2018 in Jaipur region of Rajasthan state as this region depicted to have the highest number of farmers registered under Pradhan Mantri Fasal Bima Yojana (PMFBY) in comparison to other regions of the state. A semi-structured interview schedule was used to collect the data from the respondents. The results of the study revealed that majority of the beneficiary (62.22%), non-beneficiary (64.45%) and overall respondents (63.33%) had neutral attitude towards Pradhan Mantri Fasal Bima Yojna. There was similarity found in the rank assignment pattern regarding attitude of beneficiary and non-beneficiary respondents about Pradhan Mantri Fasal Bima Yojna, though there was a difference in the magnitude of Mean Percent Scores (MPS) of beneficiary and non-beneficiary farmers. A positive and significant association was found between the attitude and some selected characteristics like education, age, occupation, exposure to mass media and contact with extension agency. The factors like caste, social participation, annual income, land holding, source of irrigation, information seeking behaviour and information sharing behaviour have not shown any significant contribution to the multiple regression analysis and were non-significantly associated with attitude of overall respondents.